Risk of venous thromboembolism occurrence among adults with selected autoimmune diseases: A study among a U.S. cohort of commercial insurance enrollees. Issue 1 (January 2015) - Yusuf, Hussain R.; Hooper, W. Craig; Grosse, Scott D.; Parker, Christopher S.; Boulet, Sheree L.; Ortel, Thomas L.
Abstract Objective This study assessed the risk of venous thromboembolism (VTE) among privately insured adults in the U.S. with one or more of the following autoimmune diseases: autoimmune hemolytic anemia (AIHA), immune thrombocytopenic purpura (ITP), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE). Materials and Methods Using the Truven Health MarketScan® Databases, patients 18–64 years of age with a diagnosis of AIHA, ITP, RA, or SLE in 2007 and a sex and age-group matched comparison group of enrollees were followed up through 2010 to identify VTE events. Survival curve and Cox proportional hazards analyses were conducted to assess differences between groups. Results Among patients with AIHA, ITP, RA, or SLE, or > 1 of these diseases, the risk of at least one VTE event was 19.74, 7.72, 4.90, 9.89, and 13.35 per 1, 000 person-years, respectively; among the comparison group, the risk was 1.91 per 1, 000 person-years. The adjusted hazard ratios (aHRs) for VTE among patients with AIHA, ITP, RA, or SLE, or > 1 of these diseases (when compared with the comparison group) tended to decline over follow-up time; at 1 year, the aHRs were 6.30 (95% confidence interval [CI]: 4.44–8.94), 2.95 (95% CI: 2.18–4.00), 2.13 (95% CI: 1.89–2.40), 4.68 (95% CI: 4.10–5.33), and 5.11 (95% CI: 4.26–6.14), respectively. Conclusion Having AIHA, ITP, RA, or SLE, or > 1 of these diseases was associated with an increased likelihood of a VTE event. More research is necessary to develop better understanding of VTE occurrence among people with autoimmune diseases.